Mental health indicators of Zacatecas migrant partner women - Lozano Razo , Georgina (Consorcio de Universidades Mexicanas A.C., 2011)
The aim of this research was to determine the differences in the score for mental health indicators of depression, hostility, interpersonal sensitivity, somatization and anxiety among women with a migrant couple residing in various municipalities of the state of Zacatecas. The sample were 146 women, residents of six municipalities of the state of Zacatecas (Jerez, Francisco R. Murguia, Monte Escobedo, General Panfilo Natera, Pinos and Villa Hidalgo). All of their couples migrated to the U.S. They were given the Symptom Assessment-45 Questionnaire (SA-45) (Sandin, Valiente, Chorot, Sante and Lostao, 1997), which is a self-reported psychopathological symptoms instrument. In this study the following subscales were administered: depression, hostility, interpersonal sensitivity, somatization and anxiety. A nonparametric test was conducted from which statistically significant differences were obtained in the anxiety subscale: women from General Pánfilo Natera produced the highest average rank (84.89) and therefore the highest levels of anxiety.